1995
DOI: 10.1159/000292417
|View full text |Cite
|
Sign up to set email alerts
|

Increased Concentrations of Lactate Dehydrogenase in Pregnancy with Preeclampsia: A Predictor for the Birth of Small-for-Gestational-Age Infants

Abstract: Lactate dehydrogenase (LDH), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) concentrations and platelet counts were measured in 26 normal pregnant women and 51 preeclamptic women. In the normal-pregnancy group, no significant changes were found in the results of these tests. In the preeclampsia group, ALT and AST concentrations were not significantly higher than those in normal pregnancy, but the LDH concentrations increased and the platelet counts decreased significantly through the pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 5 publications
1
23
1
Order By: Relevance
“…In the present study, 50% of babies had low birth weight with maternal serum LDH levels <600 IU/L where as 66 %of babies had low birth weight with maternal serum LDH levels > 600 IU/L. This indicates increase in preterm deliveries in patients with higher LDH levels .The association of low birth weight of infants with increase in serum LDH levels was suggested by He S [10] , et al in their study. This was in contrary to Qublan HS [8] , et al who did not find any significant association.…”
Section: Baby Weightsupporting
confidence: 64%
See 1 more Smart Citation
“…In the present study, 50% of babies had low birth weight with maternal serum LDH levels <600 IU/L where as 66 %of babies had low birth weight with maternal serum LDH levels > 600 IU/L. This indicates increase in preterm deliveries in patients with higher LDH levels .The association of low birth weight of infants with increase in serum LDH levels was suggested by He S [10] , et al in their study. This was in contrary to Qublan HS [8] , et al who did not find any significant association.…”
Section: Baby Weightsupporting
confidence: 64%
“…He S, Brennen K [10] et al reported that pre eclamptic women with small for gestational age infants had higher LDH concentrations than those in the appropriate for gestational age group.…”
Section: Baby Weightmentioning
confidence: 99%
“…He et al, study also proved that serum LDH were significantly higher with babies born between the gestational period of 24-29 weeks versus 30-35 weeks versus 36-40 weeks. 13,16 It also proved that low birth weights were seen in patients with higher serum LDH. Qulban et al, on contrary did not show any significant association between the low birth weight of infant and raised serum LDH levels.…”
Section: Discussionmentioning
confidence: 92%
“…They concluded that serum LDH can be a useful marker for the prediction of adverse outcome of pregnancy in severe preeclampsia. Serum LDH has also found to be a useful predictor of birth of small for gestational age infants in preeclamptic pregnancy [15]. Previous studies demonstrated the importance of amniotic serum LDH level for the prediction of fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%